Impact of CYP2C9 and VKORC1 Polymorphisms on Warfarin Sensitivity and Responsiveness in Jordanian Cardiovascular Patients during the Initiation Therapy - AL-Eitan, Laith N. (Genes (Basel), 2018)
Warfarin is an oral anticoagulant frequently used in the treatment of different cardiovascular diseases. Genetic polymorphisms in the CYP2C9 and VKORC1 genes have produced variants with altered catalytic properties. A total of 212 cardiovascular patients were genotyped for 17 Single Nucleotide Polymorphisms (SNPs) within the CYP2C9 and VKORC1 genes. This study confirmed a genetic association of the CYP2C9*3 and VKORC1 rs10871454, rs8050894, rs9934438, and rs17708472 SNPs with warfarin sensitivity. This study also found an association between CYP2C9 and VKORC1 genetic haplotype blocks and warfarin sensitivity. The initial warfarin dose was significantly related to the CYP2C9*3 polymorphism and the four VKORC1 SNPs (p < 0.001). There were significant associations between rs4086116 SNP and TAT haplotype within CYP2C9 gene and rs17708472 SNP and CCGG haplotype within VKORC1 gene and warfarin responsiveness. However, possessing a VKORC1 variant allele was found to affect the international normalized ratio (INR) outcomes during initiation of warfarin therapy. In contrast, there was a loose association between the CYP2C9 variant and INR measurements. These findings can enhance the current understanding of the great variability in response to warfarin treatment in Arabs.